PERILAKU MENYONTEK DITINJAU DARI KEPERCAYAAN DIRI - Helmi Nirwana Spayung; Winidia Marpaung; Rina Mirza (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the relationship between self-confidence and cheating behavior. The hypothesis proposed in this study is that there is a very significant negative relationship between self-confidence and cheating behavior, assuming the higher the confidence, the cheating behavior will be low. The research subjects used in this study were students of SMA Negeri X in Bangun Purba, Deli Serdang Regency, North Sumatra, as many as 213 people who were selected using Disproportionate stratified random sampling. Analysis of the data used is to use Product Moment Analysis through the help of SPSS 17 for Windows. The results of data analysis showed r = -0,484, and p = 0,000 (p <0.05) which showed that there was a very significant negative relationship between cheating behavior and self-confidence. The results of this study indicate that the contribution (R2) given the variable confidence in cheating behavior is 24.3 percent, the remaining 75.7 percent is influenced by other factors not examined. Keywords: cheating behavior, self confidence